Effect of smartphone use before bedtime on smartphone addiction behaviors among Chinese college students - Li, Linghui; Wang, Lei; Wang, Xinghua (Frontiers in Psychology, 2022)
Smartphone addiction behaviors are becoming more and more common with the rapid popularity and widespread use of smartphones. Such behaviors are significantly influenced by the overuse of smartphones before bedtime. In this study, the overuse of smartphones after 9:00 pm before bedtime was investigated by an online questionnaire. The sample consists of 1035 college students in China. The artificial neural networks were applied to predict the use time of smartphones before bedtime based on their different usages, and the relationship between smartphone usage and additive behaviors was analyzed. The results show that using short videos is more addictive as compared to other usage combinations. Meanwhile, there is a significant discrepancy in the use of smartphones before bedtime between less than half an hour and more than three hours. The artificial neural networks model has a very high prediction accuracy for both cases. These findings would help guide college students to correctly use phones and reduce smartphone addition, which is of great significance for mental health education.